MODEL – MODEL PENGELOLAAN ZAKAT DI DUNIA MUSLIM - AMIRUDDIN KUBA (El-Qist: Journal of Islamic Economics and Business (JIEB), 2014)
Role of civil society and government in managing zakah can be conducted by coordinatively and actively. The role of goverment as giving political legitimation and data sourcer in developing zakah while the institution of zakah organizer of civil society acts as excecutive in collecting and managing zakah. The relationship of both is conducted sinergictly and has direct access each other coordinatively or controlly.In practice, civil society is shaped in vertical and horizontal coordination, in which vertical coordination is held by holding company in controlling the processes of collecting and distributing zakah at organizations that responsible for doing that. On the other hand, horizontal coordination is aimed to create a cooperation among institutions. Such model of cooperation reflects an active involvement of civil society, and could strengthen the function of civil society and government.